Peningkatan Kompetensi Guru PAUD dalam Rangka Pengembangan Metode Tahsin Al Qur’an untuk Perfomansi Peserta Didik di Wilayah Kedungsepur (Kendal, Demak, Ungaran, Semarang, Purwodadi) - Dwi Mawanti; Ahmad Hasmi Hasona; Miswari Miswari (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
Community service activities such as mentoring in training methods tahsin quran aims to provide mentoring, knowledge and skills in Tahsin method for early childhood teachers for early childhood and kindergarten in kedungsepur region. This activity will be an innovative stimulus that Raudhatul Athfal and kindergarten teachers can interact and brainstorm in addressing the needs of the introduction of increasingly complex, particularly related to methods tahsin quran. The target audience in the activities is teachers Raudhatul Athfal and kindergartens in the region kedungsepur totaling 100 people. Assistance in the development of methods tahsin done with lectures, demonstrations and exercises are accompanied by question and answer. Lecture method is used to explain the concept of tahsin method. Demonstration methods used to denote a work process ie development stages tahsin learning the Qur’an, while the method of exercise to practice learning methods tahsin. While the question and answer method to allow participants to consult in overcoming obstacles in the learning method tahsin quran.The availability of sufficient expertise in the development of teaching tahsin methods for teacher’s Raudhatul Athfal or kindergartens in the region Kedungsepur, the enthusiasm of the participants, support of school principals on the implementation of activities and funding support from Islamic Higher Education Directorate of Religious Affairs in 2015 is implementation supporting these activities. The constraints faced is limited time for training.The benefits that can be obtained by the participants of this activity can know the various methods tahsin quran, such as: Nuroniyah, Qiraati, Ummi, and Yanbu'a. Kegiatan pengabdian pada masyarakat berupa pendampingan dalam pelatihan metode tahsin al-qur'an bertujuan untuk memberikan pendampingan, pengetahuan dan keterampilan dalam Metode Tahsin Untuk Anak Usia Dini Bagi Guru-Guru Paud Dan TK Di wilayah kedungsepur. kegiatan ini akan menjadi rangsangan inovatif agar para guru RA dan TK dapat saling berinteraksi dan brainstorming dalam menyikapi kebutuhan pengenalan yang kian kompleks, khususnya terkait metode tahsin al-qur'an. Khalayak sasaran dalam kegiatan PPM ini adalah guru-guru RA dan TK di wilayah kedungsepur yang berjumlah 100 orang. Pendampingan dalam pengembangan metode tahsin dilakukan dengan metode ceramah, demonstrasi dan latihan yang disertai tanya jawab. Metode ceramah digunakan untuk menjelaskan konsep metode tahsin. Metode demonstrasi dipakai untuk menunjukkan suatu proses kerja yaitu tahap-tahap pengembangan pembelajaran tahsin al-qur'an, sedangkan metode latihan untuk mempraktikkan pembelajaran metode tahsin. Sementara metode tanya jawab untuk memberi kesempatan para peserta berkonsultasi dalam mengatasi kendala dalam pembelajaran metode tahsin al-qur'an.Ketersediaan tenaga ahli yang memadai dalam pengembangan pembelajaran metode tahsin bagi guru RA dan TK di wilayah kedungsepur, antusiasme peserta, dukungan kepala sekolah terhadap pelaksanaan kegiatan dan dana pendukung dari Diktis Direktorat Pendidikan Islam Kementerian Agama tahun 2015 merupakan pendukung terlaksananya kegiatan ini. Adapun kendala yang dihadapi adalah keterbatasan waktu untuk pelatihan.Adapu manfaat yang dapat diperoleh peserta dari kegiatan ini antara lain dapat mengenal beragam metode tahsin al-quran, seperti : Nuroniyah, Qiraati, Ummi, dan Yanbu'a.